The Norwegian bureaucratic aristocracy and their manor houses in the thirteenth and fourteenth centuries - Sunde, Jørn Øyrehagen; Rogdaberg, Guttorm (Danish Journal of Archaeology, 2017)
Except royal castles in major Norwegian towns, only two stone castles were built by Norwegian aristocrats in the High Middle Ages. All other aristocrats lived in wooden buildings. Of these only Lagmannsstova at Aga in Hardanger remains. It has been attributed to the appeal court judge Sigurd Brynjulffson, though to have been constructed at the end of the thirteenth century as one unique building. However, investigations show that the remaining hall made up less than onethird of a building complex containing two halls, a chapel, kitchen and living quarters, all built at the first half of the thirteenth century. Investigations also show that the powers of the appeal court judge were drastically expanded at the same time, not at least by the Norwegian Code of the realm of 1274. By relating judicial powers and manor house, we get a quite different image of the Norwegian aristocracy and bureaucracy in the High Middle Ages than the popular one of an egalitarian peasant society.